QUESTIONS OF EARLY ADAPTIVE RADIATION OF MAMMALS - Agadjanian A.K. (My University, 2003)
Morphological and physiological differences and paleontological data suggest the independent origin of the Prototheria and the Theria. The Prototheria gave rise to the most specialized groups of Mesozoic mammals. The reasons for this are discussed. An important role in the evolutionary fate of these subclasses was played by the structural difference in the region of the middle ear, since it influenced the structure of the basicranium. The development of a perfect placental pattern in the therian stem at the end of the Cretaceous was a key character determining the fate of mammals. This gave rise to changes in the central nervous system and provided for the domination of the Placentalia in the Cenozoic.